Impelementation Of Conditional Cash Transfer (CCT) in Improving Family Welfare at Lilirawang Village Bengo District Bone Regency (Case Study : PKH In Education) - Arlina Arlina; Muhammad Guntur; Umar Nain (dialektika kontemporer, 2021)
This journal discusses the implementation of the Conditional Cash Transfer (CCT) in improving family welfare in Liliriawang Village, Bengo District, Bone Regency. The results of this study indicate that the implementation of the Conditional Cash Transfer (CCT) in improving family welfare in Liliriawang Village, Bengo District, Bone Regency, especially in the field of education is not implemented properly. This is because of the four indicators of successful policy implementation by Cheema and Rondinelli, only one indicator is running well. In addition, one of the supporting factors is the assistance provided on time and the amount in accordance with CCT provisions. for the inhibiting factor is the data used is old data, namely data from 2005 and there is no data update until now.